A four-week solubility assessment of AH-26 and four new root canal sealers - Niloofar Azadi; Arzhang Fallahdoost; Payman Mehrvarzfar; Hamid Rakhshan; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2012)
Background: The strong link between sealer solubility and periapical reinfection indicates that water solubility of new sealers should be studied. This study aimed to assess the water solubility of five root canal sealers (AH-26, Topseal, 2-Seal, Acroseal, and Roeko Seal Automix [RSA]). Materials and Methods: In this in vitro experimental study, 30 specimens were fabricated from each of the abovementioned sealants. Then they were weighed and randomly divided into three subgroups of 10 each (A, B, and C). They were set at 37°C and 100% RH, in accordance with ANSI/ADA 57 and ISO 6876-2001 requirements. Afterward, the specimens in subgroups A were incubated at 37°C and 100% RH for 24 hours, while the specimens in the subgroups B and C were incubated in the same conditions for 7 days and 28 days, respectively. After incubation, the specimens were dried with blotting paper and were incubated for 24 hours at 37°C and 0% RH. Then they were weighed. The percentage of weight loss was regarded as water solubility. Results: The mean solubility of the sealers AH-26, Acroseal, Topseal, 2-Seal, and RSA were 0.28%, 0.36%, 0.07%, 0.037%, and 0.141% after 24 hours, respectively. After 28 days, their solubility were 1.75%, 0.746%, 0.082%, 0.04%, and 0.517%, respectively. Only the solubility of the sealers 2-Seal and Topseal were not statistically different (P>0.3 [Tukey's]). Again only the solubility of 2-Seal and Topseal did not significantly increase between the 7 th day and the 28 th day of incubation (P>0.6 [paired-samples t]). Conclusion: All tested materials met the standards (maximum weight loss of 3% within 24 hours). However, the results of 2-Seal followed by Topseal were the most favorable ones.